Exploring postpartum women’s experiences, perspectives, and expectations in maternal health care at a Chinese maternity care center: a qualitative study - Xiaoqian Zhang; Yang Liu; Tang Li; Frank Buntinx; Mieke Vermandere (BMC Pregnancy and Childbirth)
Abstract Background The postpartum period presents critical challenges for new mothers, involving significant physical and emotional adjustments. Traditionally, Chinese culture has addressed this phase through “doing the month,” emphasizing rest and specific cultural practices. Modernization in urban China has led to a rise in professional maternal care centers, yet research on women’s experiences and expectations in these settings remains limited. This study aims to explore the experiences, perspectives, and expectations of postpartum women who utilize hospital-based maternity care centers, focusing on the integration of traditional practices with modern healthcare standards. Methods In this study, 16 participants who had utilized the hospital’s maternal care center within the previous year were chosen via purposive sampling in Qingdao, China. Data were collected through semi-structured interviews and analyzed employing The Qualitative Analysis Guide of Leuven (QUAGOL), a framework ensuring transparency and depth in identifying and interpreting themes. Results Analysis revealed three main themes: co-created health management, shared knowledge and growth, and interpersonal connections and support. The study highlighted the benefits of a collaborative approach to healthcare, where personalized care and maternal autonomy were prioritized. It also pointed out the educational aspect of motherhood, emphasizing the role of community support and shared experiences. Furthermore, the study highlighted the positive impact of social dynamics, such as family, peer, and professional support, emphasizing their crucial contribution to the postpartum recovery process. Conclusion This study underscores the importance of integrating traditional postpartum practices with modern healthcare, focusing on co-created health management, shared knowledge and growth, and interpersonal connections and support. These elements significantly enhance maternal well-being, addressing both physical and psychosocial needs. These results highlight the importance of culturally sensitive care tailored to the societal and cultural contexts of postpartum women in China. Practical recommendations include enhancing personalized care models and strengthening support networks within healthcare systems to better meet mothers’ needs. These findings provide a foundation for improving postpartum care policies and practices, with implications for creating more supportive environments for new mothers. Future studies are encouraged to expand the participant diversity, explore diverse cultural settings, and apply quantitative methods to validate these outcomes.